Bald eagle search algorithm based optimal reconfiguration of centralized Thermoelectric Generation System under non-uniform temperature distribution condition - Zhang, Minhao; Fang, Xia (Frontiers in Energy Research, 2022)
Fossil energy is becoming increasingly scarce, and technological innovation to promote clean energy consumption and achieve the “dual carbon” goal has increasingly become the focus of discussion. Compared with the full coverage thermoelectric module design scheme, the optimized layout scheme uses fewer thermoelectric generation (TEG) modules, thus confirming that the more TEG modules that are not arranged, the better. This research provides a possible way to improve the output power of TEG system. This paper proposed a bald eagle search algorithm (BES) scheme to optimize centralized TEG array reconfigures, which has not been previously employed to achieve a fast and effective tracking of the maximum power point tracking (MPPT) under non-uniform temperature difference (NTD) condition. In order to efficiently seek the global MPP (GMPP) under NTD condition, a BES algorithm is adopted to TEG reconfigures arrays to evidently improve the global searching ability of BES algorithm through the previous searching results. Furthermore, the main method in this paper is preliminarily verified on MATLAB. Both simulation and experimental results show that BES algorithm can significantly improve the convergence accuracy and output power.